1976
DOI: 10.1002/hlca.19760590830
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Isomerizations of Bicyclo[2.1.0]pent‐5‐yl Methyl Ketones: endo‐exo stereomutation and cyclopropyl‐allylic rearrangement to cyclopent‐2‐enyl methyl ketones

Abstract: Bicyclo[2.1.0]pent-5-y1 methyl ketones undergo endo-exo stereomutation and cyclopropyl-allylic rearrangement to cyclopent-2-enyl methyl ketones at temperatures above ca. 130" in inert solvents. These isornerizations are not accompanied by any other detectable thermal processes. The stereomutation has been described first by Jorgenson & Thacher [2] for the (1,5-dimethylbicyclopent-5-y1) methyl ketones, and the rearrangement was encountered simultaneously by these authors with the same compounds and by ourselve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The formation of the thermally labile [34] oxadi-n-methane-rearrangement products on direct irradiation, which remained below reliable detection limits in the first photochemical study of Ib [3], has now been demonstrated by the use of improved analytical conditions. Figure 3.…”
mentioning
confidence: 99%
“…The formation of the thermally labile [34] oxadi-n-methane-rearrangement products on direct irradiation, which remained below reliable detection limits in the first photochemical study of Ib [3], has now been demonstrated by the use of improved analytical conditions. Figure 3.…”
mentioning
confidence: 99%
“…37b). A precedent for such a I rearrangement is found in the thermal rearrangement of 38 to 39 (23), which on the basis of kinetic evidence has been proposed to involve a concerted I ,2, + ,2, process analogous to that shown in 37a. In the present case the observation of the formation of only the AIB-cis isomer provides some grounds for favoring the concerted mechanism.…”
mentioning
confidence: 99%